Effect of Range of Motion Exercise on Extremity Joint Muscle Strength in Ischemic Stroke Patients a Literature review - Nasim, Nasim; Nani, Desiyani (STIKep PPNI Jawa Barat, 2024)
Aims: Muscle strength and Range of Motion (ROM) are very important for ischemic stroke patients because they can prevent contractures, and increase the muscle strength of ischemic stroke patients. Range of motion (ROM) exercises in the upper extremities can increase muscle strength so that post-stroke patients can perform Activities of Daily Living independently. Objective: To know about the effect of the effectiveness of ROM with various methods to increase muscle strength and range of motion of joints. Method: Literature review to determine range of motion exercise on limb joint muscle strength in ischemic stroke patients with 5 articles with 4 data search tools: PubMed, NCBI, Science Direct, and Proquest. The inclusion criteria were patients who had an ischemic stroke, randomized control trials, and the full text available in a literature review published in the last five years, i.e. 2018-2023, articles in English. Results: From the articles obtained, 556 articles were found Research campresearch searched in accordance with creteria found 5 articles on the effect of range of motion exercise on muscle strength of the extremity joints in ischemic stroke patients. Positive results were obtained from the benefits of muscle strength and ROM. Clinical evidence was obtained from five journals analyzed that there was an increase in strength and range of motion and there were differences in the results of the experimental group and the control group. Conclusion: The provision of ROM intervention techniques is proven to increase muscle strength and joint range of motion in ischemic stroke patients, so as to help patients in the process of maintaining muscle strength and joint range of motion. In the future, this activity can be done independently by patients at home.